Gastroduodenal intussusception and pylorus obstruction induced by a c-KIT-negative gastric gastrointestinal stromal tumor: case report and review of the literature - Zhou, Yong; Wu, Xu-Dong; Shi, Quan; Xu, Chuan-hai; Jia, Jing (Zeitschrift für Gastroenterologie, 2018)
Introduction Gastrointestinal stromal tumors (GISTs) are infrequently reported to cause gastroduodenal intussusception, especially in the cases with complete pylorus obstruction. GISTs comprise only 1 – 3 % of all gastrointestinal tract tumors, and most of them strongly express the c-KIT protein. Approximately 5 % of GISTs show negative staining of c-KIT.Case presentation A 69-year-old man complained of acute abdominal pain accompanied with nausea and vomiting for 6 hours. Emergency endoscopic examination, upper gastroenterography, and computed tomography scan suggested gastroduodenal intussusception and pylorus obstruction induced by a gastric GIST. Laparoscopic exploration and wedge resection of the tumor were performed in the patient. Postoperative histological examination showed a gastric GIST with c-KIT-negative expression.Conclusion Herein, we report the unique findings of a c-KIT-negative gastric GIST presenting with gastroduodenal intussusception and pylorus obstruction. We also reviewed the English language literature of gastroduodenal intussusception induced by GISTs and put our case in the context of the previously reported cases.
Keywords: GIST; c-KIT-negative; gastroduodenal intussusception; pylorus obstruction